Analisis Sejarah Hukum Terhadap Perubahan Atas Undang Undang Tentang Perlindungan Anak - Marune, Abraham Ethan Martupa Sahat (Ulumul Syar'i : Jurnal Ilmu-Ilmu Hukum dan Syariah, 2023)
This study aims to analyze the legal history of Law Number 35 of 2014 which is an amendment to Law Number 23 of 2002 concerning Child Protection. This analysis will identify existing legal gaps in the law, taking into account the historical context and evolution of child protection law in Indonesia. This study uses a normative juridical research method and is descriptive-analytical. The main data used are laws related to child protection, including Law Number 35 of 2014 and Law Number 23 of 2002. In addition, historical documents, court decisions, and related literature are also analyzed to understand the context and interpretation of the law used. relevant. Data collection techniques involve literature study and document search. The results of the study show that the legal history of changes to child protection laws is due to significant changes in terms of social development, paradigm shifts, and increased awareness of children's rights related to child protection arrangements. The focus of the application of child protection law boils down to fulfilling optimal protection for witnesses and victims where the current conditions make it possible for violence and sexual crimes to occur, the perpetrators of which are children.